The Asian clam Corbicula fluminea in the European freshwater-dependent industry: a latent threat or a friendly enemy? - Rosa, Inês C. (2020)
While the biofouler Corbicula fluminea (Müller, 1774) is known to cause great economic losses in North America, studies reporting the problem in Europe are much scarcer. This paper explores the industrial effects of the species in Portugal, the gateway by which the bivalve entered Europe around 30 years ago. National waterworks, major power stations, cement plants, pulp and paper mills and irrigation systems were surveyed. The industrial impacts of the pest were shown to remain relatively mild; irrigation systems are those that seem to be facing more significant economic losses due to infestation. Possible reasons for the apparent discrepancy between this result and the species dispersal in natural ecosystems are discussed, and recommendations on adequate responses to the latent threat are provided. This study may assist the implementation of integrated pest management policies in countries at risk of invasion or recently invaded, and contribute to an understanding of the species’ progression in industrial environments.